2015
DOI: 10.1051/0004-6361/201424946
|View full text |Cite
|
Sign up to set email alerts
|

ASteCA: Automated Stellar Cluster Analysis

Abstract: We present the Automated Stellar Cluster Analysis package (ASteCA), a suit of tools designed to fully automate the standard tests applied on stellar clusters to determine their basic parameters. The set of functions included in the code make use of positional and photometric data to obtain precise and objective values for a given cluster's center coordinates, radius, luminosity function and integrated color magnitude, as well as characterizing through a statistical estimator its probability of being a true phy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
121
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(135 citation statements)
references
References 141 publications
(113 reference statements)
1
121
0
4
Order By: Relevance
“…It provides input for population synthesis models to study resolved and unresolved star clusters and galaxies (e.g. Perren, Vázquez & Piatti 2015;Gutkin, Charlot & Bruzual 2016;Chevallard & Charlot 2016), and offers reliable models for many other field of studies, such as to derive black hole mass when observing gravitational waves (e.g. Spera, Mapelli & Bressan 2015;Belczynski et al 2016), to get host star parameters for exoplanets (Santos et al 2013;Maldonado et al 2015, etc.…”
Section: Introductionmentioning
confidence: 99%
“…It provides input for population synthesis models to study resolved and unresolved star clusters and galaxies (e.g. Perren, Vázquez & Piatti 2015;Gutkin, Charlot & Bruzual 2016;Chevallard & Charlot 2016), and offers reliable models for many other field of studies, such as to derive black hole mass when observing gravitational waves (e.g. Spera, Mapelli & Bressan 2015;Belczynski et al 2016), to get host star parameters for exoplanets (Santos et al 2013;Maldonado et al 2015, etc.…”
Section: Introductionmentioning
confidence: 99%
“…We give in Sect. 2.9 of Perren et al (2015, hereafter Paper I) a non-exhaustive list of articles in which these methods were employed. Still, by-eye studies continue to be used.…”
Section: Introductionmentioning
confidence: 99%
“…The code includes functions to perform cluster structure analysis, luminosity function curves, integrated colour estimates statistically cleaned from field star contamination, a Bayesian membership assignment algorithm, and a synthetic clusterbased best isochrone matching method to simultaneously estimate clusters' properties (age, metallicity, distance, reddening, mass and binarity). Perren, Vázquez & Piatti (2015) showed that it does not introduce any biases or new correlations between the various derived cluster parameter values.…”
Section: Synthetic Colour-magnitude Diagramsmentioning
confidence: 95%